2005
DOI: 10.1212/01.wnl.0000148725.48740.6d
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic dysfunction in unrelated, asymptomatic carriers of a single parkin mutation

Abstract: Parkin disease is usually autosomal recessive; however, two studies have shown that asymptomatic heterozygotes have nigrostriatal dysfunction and even manifest subtle extrapyramidal signs. The authors used 18F-dopa PET to study 13 asymptomatic parkin heterozygotes and found a significant reduction of (18)F-dopa uptake in caudate, putamen, ventral, and dorsal midbrain compared with control subjects. Four had subtle extrapyramidal signs. Parkin heterozygosity is a risk factor for nigrostriatal dysfunction and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(96 citation statements)
references
References 10 publications
4
88
0
4
Order By: Relevance
“…This is mostly supported by neurophysiological and functional neuroimaging studies, that showed significant albeit subclinical signs of dopaminergic dysfunction in healthy carriers of Parkin and PINK1 single mutations (reviewed in Klein et al, 2007). A role for these variants as PD susceptibility factors would justify their higher frequency among our patients with positive family history of unclear inheritance (6.5%), and their occurrence also in healthy subjects and in individuals with very mild parkinsonian signs (Khan et al, 2005;Hedrich et al, 2006). Yet, it is presently unknown whether the subclinical abnormalities found in healthy heterozygotes are going to remain stable or to evolve towards a clinically manifest phenotype.…”
Section: Discussionmentioning
confidence: 57%
“…This is mostly supported by neurophysiological and functional neuroimaging studies, that showed significant albeit subclinical signs of dopaminergic dysfunction in healthy carriers of Parkin and PINK1 single mutations (reviewed in Klein et al, 2007). A role for these variants as PD susceptibility factors would justify their higher frequency among our patients with positive family history of unclear inheritance (6.5%), and their occurrence also in healthy subjects and in individuals with very mild parkinsonian signs (Khan et al, 2005;Hedrich et al, 2006). Yet, it is presently unknown whether the subclinical abnormalities found in healthy heterozygotes are going to remain stable or to evolve towards a clinically manifest phenotype.…”
Section: Discussionmentioning
confidence: 57%
“…The pattern of dopaminergic deficit in symptomatic parkin patients mimics that of idiopathic PD, putamen being targeted, but the caudate and midbrain are relatively more involved (59). Asymptomatic heterozygote parkin gene carriers also show a mild but significant reduction in putamen 18 F-dopa uptake (60). This dopaminergic deficit could conceivably make heterozygote carriers more susceptible to late-onset PD.…”
Section: Detection Of Preclinical Pdmentioning
confidence: 97%
“…These parkin mutations include exonic deletion, duplication, and triplication as well as several missense/ nonsense substitutions. Although initially described as a recessive disorder, emerging evidence suggest that heterozygous parkin mutations may confer increased susceptibility to PD (Hilker et al, 2001(Hilker et al, , 2002Oliveira et al, 2003;Khan et al, 2005;L. N. Clark et al, 2006;Sun et al, 2006).…”
Section: Introductionmentioning
confidence: 99%